Yokohama : Reinventing the Future of a City - Tokyo Development Learning Center (Washington, DC: World Bank, 2018)
The intent of the two competitive cities case studies is to highlight what institutions and strategies successful cities have relied on to spur economic development, under what conditions such success has occurred, and what lessons of this experience might be applicable to decision makers in other cities. This research was prepared by the Tokyo Development Learning Center (TDLC) under the auspices of the Social, Urban, Rural, and Resilience Global of the World Bank Group. Its objective is to create a knowledge base on what makes cities competitive, understand job creation at the city level, and capture the unique development experience of Japan for broad dissemination to development practitioners, government officials, academia and the private sector. The team would like to gratefully acknowledge the Government of Japan and its continued support of the Tokyo Development Learning Center (TDLC) program.